Composite lithium metal negative plate as well as preparation method and application thereof
By growing MOF materials on the surface of the solid electrolyte and filling with liquid lithium metal, the problem of interface resistance between metal lithium and solid electrolyte is solved, the interface wetting and conductivity are significantly improved, dendrites are inhibited, and the stability of the battery is enhanced.
Patent Information
- Application Number
- CN202510042016.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
AI Technical Summary
In solid-state lithium batteries, there is a huge ion transmission resistance at the interface between metal lithium and solid electrolyte, resulting in uneven ion transmission paths and excessive local current, which accelerates the growth of lithium dendrites, and eventually leads to a short circuit in the battery.
Lithophilic MOF material is grown in situ on the surface of the porous solid electrolyte, and liquid lithium metal is uniformly filled in the pores of LLZTO through melt infusion technology to form a composite lithium metal negative electrode sheet.
It significantly improves the interface wetting of metal lithium and solid electrolyte, inhibits dendrites' growth, and improves the overall conductivity and stability of the electrolyte.
Smart Images

Figure CN119812215A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and more specifically, to a composite lithium metal negative electrode sheet and a preparation method and application thereof. Background Art
[0002] Compared with liquid electrolytes, solid electrolytes have the advantages of high safety, low leakage, and low flammability. Therefore, applying them to lithium-ion batteries can effectively avoid safety hazards caused by leakage and combustion. They have great potential and market for use in power batteries with higher safety requirements.
[0003] Due to the huge specific surface energy between molten lithium metal and solid electrolyte, lithium metal cannot spread on the surface of solid electrolyte, resulting in huge ion transfer resistance (up to 2319Ω·cm) between solid electrolyte and lithium metal. -2 ), and poor contact between the molten metal lithium and the solid electrolyte interface causes uneven ion transmission paths, which leads to excessive local current, accelerates the growth of lithium dendrites, and ultimately causes battery short circuit. Therefore, how to solve the interface problem between the solid electrolyte and the metal lithium negative electrode while maintaining the advantages of the solid electrolyte has become a technical problem that needs to be solved urgently in the current field of solid-state lithium batteries.
[0004] In order to overcome this technical difficulty, technicians in this field have tried a variety of solutions. For example, through interface modification, alloying reactions of lithium with other metals (such as gold, magnesium, titanium, etc.) are used to generate alloy layers such as Li-Au, Li-Mg, and Li-Ti, which can significantly reduce the interface resistance. However, the method of plating a nanolayer (such as Al2O3) on the surface of LLZTO using techniques such as atomic layer deposition and magnetron sputtering is effective but the process is complex and costly, making it difficult to apply on a large scale. Another method is to introduce an intermediate layer, such as modifying the surface of LLZTO ceramic electrolyte with a gel electrolyte to obtain a flexible interface, but the gel electrolyte is greatly affected by temperature, and its conductivity and interface impedance will increase at low temperatures. Although these methods can improve the wettability of LLZTO and inhibit dendrite growth to a certain extent, lithium may still penetrate the electrolyte material under high current density or long-term cycling conditions, resulting in short circuit problems. Therefore, exploring more efficient, economical and stable solutions is of great significance for promoting the widespread application of solid electrolytes in lithium-ion batteries. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a composite lithium metal negative electrode sheet and a preparation method and application thereof. The present invention grows a lithium-philic MOF material in situ on the surface of a porous solid electrolyte and adopts a melt infusion technology to uniformly fill liquid lithium metal in the porous LLZTO pores, thereby significantly improving the interface wettability of metallic lithium and solid electrolyte, inhibiting dendrite growth, and having good stability.
[0006] The present invention provides a composite lithium metal negative electrode sheet, comprising a porous solid electrolyte layer, a lithium-philic layer composited on one side of the porous solid electrolyte layer, and a metal lithium layer composited on the other side of the porous solid electrolyte layer; the porous solid electrolyte layer has pores, the lithium-philic layer is at least partially embedded in the pores, and forms a conductive porous solid electrolyte skeleton with the porous solid electrolyte as a whole; the metal lithium layer at least partially fills the pores and forms a covering layer;
[0007] The lithium-philic layer contains a metal oxide derived from a MOF and is formed by carbonizing a MOF material grown in situ on the surface of the porous solid electrolyte layer.
[0008] Preferably, the porous solid electrolyte layer has a porosity of 40% to 80%, a pore size of 1 μm to 20 μm, and a thickness of 25 μm to 30 μm.
[0009] Preferably, the MOF material is selected from one or more of Zr-MOF, Sn-MOF, Mn-MOF, ZIF-8, ZIF-67, MIL-101, and MIL-100.
[0010] Preferably, the thickness of the composite lithium metal negative electrode sheet is 40 μm to 80 μm;
[0011] The thickness of the lithium-philic layer is 10 μm to 20 μm;
[0012] The thickness of the conductive porous solid electrolyte skeleton is 30 μm to 50 μm;
[0013] The thickness of the covering layer is 10 μm to 30 μm.
[0014] The present invention also provides a method for preparing the composite lithium metal negative electrode sheet described in the above technical solution, comprising the following steps:
[0015] a) mixing a solid electrolyte, a pore-forming agent, a film-forming agent and a solvent, and drying the mixture to obtain a mixed slurry; and then sequentially forming and sintering the mixed slurry to obtain a porous solid electrolyte layer;
[0016] b) in-situ growing a MOF material on the surface of the porous solid electrolyte layer obtained in step a), and obtaining a conductive porous solid electrolyte skeleton after carbonization;
[0017] c) melting and pouring metallic lithium into the conductive porous solid electrolyte skeleton obtained in step b) to fill the pores and form a covering layer to obtain a composite lithium metal negative electrode sheet.
[0018] Preferably, the solid electrolyte in step a) is LLZTO material; the preparation method of the LLZTO material is specifically as follows:
[0019] LiOH·H2O, La2O3, ZrO2 and Ta2O5 are mixed, solid-phase sintered and then ground to obtain LLZTO material;
[0020] The solid phase sintering is carried out at a temperature of 900° C. to 1000° C. and for a time of 4 to 6 hours.
[0021] Preferably, in step a), the pore-forming agent is selected from one or more of glucose, sucrose, urea, starch, and citric acid; the film-forming agent is selected from polyethersulfone and / or polyvinylidene fluoride; and the solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, and anhydrous ethanol;
[0022] The mass ratio of the solid electrolyte, pore former and film former is 1:(0.1-0.2):(0.05-0.2);
[0023] The drying temperature is 150°C to 250°C and the drying time is 20h to 30h;
[0024] The molding pressure is 15MPa to 300MPa;
[0025] The sintering temperature is 1000° C. to 1200° C., and the sintering time is 6 h to 24 h.
[0026] Preferably, the in-situ growth method in step b) is: subjecting the porous solid electrolyte to a hydrothermal reaction in a MOF precursor solution; the hydrothermal reaction temperature is 20° C. to 180° C., and the time is 8 h to 24 h;
[0027] The carbonization heating rate is 1°C / min to 5°C / min, the temperature is 280°C to 500°C, and the time is 2h to 4h.
[0028] Preferably, the process of melt infusion in step c) is specifically as follows:
[0029] After the conductive porous solid electrolyte skeleton is brought into contact with the metal lithium sheet, the metal lithium sheet is heated to melt, and the molten metal lithium partially fills the pores through adsorption to form a covering layer.
[0030] The present invention also provides a lithium battery, which uses the composite lithium metal negative electrode sheet described in the above technical solution as a negative electrode.
[0031] The present invention provides a composite lithium metal negative electrode sheet and a preparation method and application thereof; the composite lithium metal negative electrode sheet comprises a porous solid electrolyte layer, a lithium-philic layer composited on one side of the porous solid electrolyte layer, and a metal lithium layer composited on the other side of the porous solid electrolyte layer; the porous solid electrolyte layer has pores, the lithium-philic layer is at least partially embedded in the pores, and forms a conductive porous solid electrolyte skeleton with the porous solid electrolyte as a whole; the metal lithium layer at least partially fills the pores and forms a covering layer; the lithium-philic layer contains a metal oxide derived from MOF, and is formed by carbonization of MOF material grown in situ on the surface of the porous solid electrolyte layer. Compared with the prior art, the composite lithium metal negative electrode sheet provided by the present invention adopts a specific layer structure of specific materials to achieve better overall interaction: on the one hand, the porous structure of the porous solid electrolyte layer can effectively increase the specific surface area, increase the contact area with lithium metal, and enhance the conduction channel of lithium ions, while also being able to improve the bonding strength with both sides. The lithium affinity of the MOF-derived material and the pore structure of the porous solid electrolyte can promote the uniform deposition of lithium metal and improve the problem of lithium dendrite growth. The above factors achieve a synergistic effect, thereby being able to enhance the overall conductivity of the electrolyte; on the other hand, the addition of MOF can improve the chemical contact between lithium metal and the solid electrolyte, and the lithium affinity of MOF effectively reduces the interfacial binding energy between Li and the solid electrolyte, making it easier for lithium metal to combine with the electrolyte surface to form a more stable interface; ultimately, the interfacial wettability of metallic lithium and the solid electrolyte is significantly improved, dendrite growth can be inhibited, and the stability is good.
[0032] At the same time, the preparation method provided by the present invention has a clear and concise overall process route, easily controllable conditions, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram of the structure of the composite lithium metal negative electrode sheet provided by the present invention;
[0034] Figure 2 A SEM image of a cross section of a porous solid electrolyte provided by the present invention;
[0035] Figure 3 The overall process flow chart of the preparation method provided by the embodiment of the present invention;
[0036] Figure 4 A schematic diagram of button-type battery assembly according to an application example of the present invention;
[0037] Figure 5 The long cycle performance of the Co3O4@LLZTO@Li||LFP full battery at 0.2C in Example 2 of the present invention;
[0038] Figure 6This is the rate diagram of the Co3O4@LLZTO@Li||LFP full battery at 0.2C to 3C in Example 2 of the present invention;
[0039] Figure 7 This is the CV performance of the Co3O4@LLZTO@Li||LFP full battery in Example 2 of the present invention. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The present invention provides a composite lithium metal negative electrode sheet, comprising a porous solid electrolyte layer, a lithium-philic layer composited on one side of the porous solid electrolyte layer, and a metal lithium layer composited on the other side of the porous solid electrolyte layer; the porous solid electrolyte layer has pores, the lithium-philic layer is at least partially embedded in the pores, and forms a conductive porous solid electrolyte skeleton with the porous solid electrolyte as a whole; the metal lithium layer at least partially fills the pores and forms a covering layer;
[0042] The lithium-philic layer contains a metal oxide derived from a MOF and is formed by carbonizing a MOF material grown in situ on the surface of the porous solid electrolyte layer.
[0043] See also Figure 1 , Figure 1 This is a schematic structural diagram of the composite lithium metal negative electrode sheet provided by the present invention, wherein 1 is a lithium-philic layer, 2 is a porous solid electrolyte layer, and 3 is a metal lithium layer; the lithium-philic layer is on the surface of the porous solid electrolyte layer, and the metal lithium layer is located at the bottom layer.
[0044] In the present invention, the composite lithium metal negative electrode sheet includes a porous solid electrolyte layer, a lithium-philic layer composited on one side of the porous solid electrolyte layer, and a metal lithium layer composited on the other side of the porous solid electrolyte layer. It is preferably composed of a porous solid electrolyte layer, a lithium-philic layer composited on one side of the porous solid electrolyte layer, and a metal lithium layer composited on the other side of the porous solid electrolyte layer.
[0045] In the present invention, the porous solid electrolyte layer has pores, and the pores are preferably micrometer-level; the porosity of the porous solid electrolyte layer is preferably 40% to 80%, the pore size is preferably 1 μm to 20 μm, and the thickness is preferably 25 μm to 30 μm.
[0046] In the present invention, the lithium-philic layer is at least partially embedded in the pores, and forms a conductive porous solid electrolyte skeleton with the porous solid electrolyte as a whole. In the present invention, the thickness of the conductive porous solid electrolyte skeleton is preferably 30 μm to 50 μm.
[0047] In the present invention, the lithium-philic layer contains a metal oxide derived from MOF (denoted as M x O y ), formed by carbonization of MOF material grown in situ on the surface of the porous solid electrolyte layer. In the present invention, the MOF material is preferably selected from one or more of Zr-MOF, Sn-MOF, Mn-MOF, ZIF-8, ZIF-67, MIL-101, and MIL-100, and more preferably Sn-MOF, Mn-MOF, or ZIF-67.
[0048] In the present invention, the metal lithium layer at least partially fills the pores and forms a covering layer; the thickness of the covering layer is preferably 10 μm to 30 μm; on this basis, the thickness of the composite lithium metal negative electrode sheet is preferably 40 μm to 80 μm.
[0049] The composite lithium metal negative electrode sheet provided by the present invention adopts a specific layer structure of specific materials to achieve better overall interaction, can significantly improve the interface wettability of metal lithium and solid electrolyte, inhibit dendrite growth, and has good stability.
[0050] The present invention also provides a method for preparing the composite lithium metal negative electrode sheet described in the above technical solution, comprising the following steps:
[0051] a) mixing a solid electrolyte, a pore-forming agent, a film-forming agent and a solvent, and drying the mixture to obtain a mixed slurry; and then sequentially forming and sintering the mixed slurry to obtain a porous solid electrolyte layer;
[0052] b) in-situ growing a MOF material on the surface of the porous solid electrolyte layer obtained in step a), and obtaining a conductive porous solid electrolyte skeleton after carbonization;
[0053] c) melting and pouring metallic lithium into the conductive porous solid electrolyte skeleton obtained in step b) to fill the pores and form a covering layer to obtain a composite lithium metal negative electrode sheet.
[0054] The present invention firstly mixes a solid electrolyte, a pore former, a film former and a solvent, and then dries the mixture to obtain a mixed slurry; then the mixed slurry is successively molded and sintered to obtain a porous solid electrolyte.
[0055] In the present invention, the solid electrolyte is preferably LLZTO material; in a preferred embodiment of the present invention, the LLZTO material is prepared by solid phase reaction method from LiOH·H2O, La2O3, ZrO2 and Ta2O5 according to a stoichiometric ratio; the preparation method of the LLZTO material is preferably specifically as follows:
[0056] LiOH·H2O, La2O3, ZrO2 and Ta2O5 are mixed, solid-phase sintered and then ground to obtain LLZTO material. The present invention has no special restrictions on the sources of the LiOH·H2O, La2O3, ZrO2 and Ta2O5, and commercially available products known to those skilled in the art can be used.
[0057] In the present invention, the amounts of LiOH·H2O, La2O3, ZrO2 and Ta2O5 are preferably set according to the stoichiometric ratio of the LLZTO material, wherein 5% to 15% of LiOH·H2O is additionally added to compensate for the volatilization of lithium during the sintering process.
[0058] In the present invention, the temperature of the solid phase sintering is preferably 900°C to 1000°C, specifically 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C; the time of the solid phase sintering is preferably 4h to 6h, specifically 4h, 5h, 6h; after solid phase sintering, LLZTO powder is obtained by sufficient grinding.
[0059] In the present invention, the pore-forming agent is preferably selected from one or more of glucose, sucrose, urea, starch, and citric acid, and starch is more preferred; the film-forming agent is preferably selected from polyethersulfone and / or polyvinylidene fluoride, and polyethersulfone or polyvinylidene fluoride is more preferred; the solvent is preferably selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, and anhydrous ethanol, and anhydrous ethanol is more preferred. The present invention has no special restrictions on the sources of the above-mentioned pore-forming agent, film-forming agent, and solvent, and commercially available products known to those skilled in the art can be used.
[0060] In the present invention, the mass ratio of the solid electrolyte, pore former and film former is preferably 1:(0.1-0.2):(0.05-0.2); the amount of the solvent is preferably sufficient to ensure that the above raw materials can be ground into slurry.
[0061] In the present invention, the drying temperature is preferably 150°C to 250°C, specifically 150°C, 200°C, 250°C; the drying time is preferably 20h to 30h, specifically 20h, 22h, 24h, 26h, 28h, 30h; after drying, the solvent is removed to obtain a mixed slurry.
[0062] In the present invention, the molding pressure is preferably 15 MPa to 300 MPa, specifically 15 MPa, 30 MPa, 50 MPa, 100 MPa, 200 MPa, 300 MPa.
[0063] In the present invention, the sintering process is preferably carried out in a muffle furnace; the sintering temperature is preferably 1000°C to 1200°C, specifically 1000°C, 1050°C, 1100°C, 1150°C, 1200°C; the sintering time is preferably 6h to 24h, specifically 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h.
[0064] After obtaining the porous solid electrolyte, the present invention in-situ grows MOF material on the surface of the obtained porous solid electrolyte layer, and obtains a conductive porous solid electrolyte skeleton after carbonization.
[0065] In the present invention, the in-situ growth method is preferably: subjecting the porous solid electrolyte to a hydrothermal reaction in a MOF precursor solution. The present invention has no special restrictions on the type and source of the MOF precursor solution, and the self-made MOF precursor solution of the corresponding MOF precursor solution of different types of MOF materials can be prepared by the above-mentioned technical scheme well known to those skilled in the art. In the present invention, the concentration of the MOF precursor solution is preferably 0.25mol / L to 0.75mol / L, specifically 0.25mol / L, 0.5mol / L, 0.75mol / L.
[0066] In the present invention, the hydrothermal reaction process is preferably carried out in a polytetrafluoroethylene reactor familiar to those skilled in the art; the temperature of the hydrothermal reaction is preferably 20°C to 180°C, specifically 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C; the time of the hydrothermal reaction is preferably 8h to 24h, specifically 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h; after the hydrothermal reaction, the product is taken out and dried, that is, the MOF material is in situ grown on the surface of the porous solid electrolyte layer, and the product is further carbonized.
[0067] In the present invention, the heating rate of the carbonization is preferably 1°C / min to 5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min; the carbonization temperature is preferably 280°C to 500°C, specifically 280°C, 300°C, 350°C, 400°C, 450°C, 500°C; the carbonization time is preferably 2h to 4h, specifically 2h, 3h, 4h; after carbonization, take it out and cool it naturally to obtain a conductive porous solid electrolyte skeleton.
[0068] The conductive porous solid electrolyte skeleton is obtained. The present invention melts and infuses metallic lithium into the conductive porous solid electrolyte skeleton to fill the pores and form a covering layer to obtain a composite lithium metal negative electrode sheet.
[0069] The present invention has no special limitation on the source of the metallic lithium, and commercially available products known to those skilled in the art may be used.
[0070] In the present invention, the process of melt infusion is preferably as follows:
[0071] After the conductive porous solid electrolyte skeleton is brought into contact with the metal lithium sheet, the metal lithium sheet is heated to melt, and the molten metal lithium partially fills the pores through adsorption to form a covering layer.
[0072] In the present invention, the above-mentioned melt infusion process is preferably carried out in a glove box filled with inert gas; the inert gas includes but is not limited to nitrogen and / or argon.
[0073] In the present invention, the specific operation of the contact is preferably: the MOF-coated porous solid electrolyte (i.e., the conductive porous solid electrolyte skeleton) is used as a frame to tightly press against the metallic lithium in the lower layer; stainless steel is then used as a reaction container to heat the metallic lithium to melt, and the liquid metallic lithium is infiltrated into the surface and pores of the porous solid electrolyte layer by adsorption.
[0074] In the present invention, the temperature of heating the metal lithium sheet to melt is preferably 180°C to 220°C, more preferably 200°C, at which temperature liquid metal lithium can be obtained, and the liquid metal lithium will enter the porous solid electrolyte to fill the pores and form a coating layer, and finally form a composite lithium metal negative electrode sheet. In a preferred embodiment of the present invention, the composite lithium metal negative electrode sheet can be recorded as M x O y @LLZTO@Li.
[0075] In the present invention, the lithium metal loading per unit area of the porous solid electrolyte is preferably 5wt% to 10wt%, specifically 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%.
[0076] The preparation method provided by the present invention innovatively uses LLZTO as a solid electrolyte, forms micron-scale pores on the surface of LLZTO by using a pore-forming agent; then, using porous LLZTO as a framework, in-situ grows MOF material on its surface, and carbonizes to form a lithium-philic layer to obtain a porous LLZTO coated with a lithium-philic oxide; then, using a melt infusion technique, molten liquid lithium is infiltrated into the pores of LLZTO, thereby uniformly filling the porous LLZTO pores with liquid lithium metal, and forming a coating layer, and finally obtaining a composite lithium metal negative electrode sheet. In addition, when a solid electrolyte is used in a system with a melting point higher than lithium (180°C) or a lithium alloy, a liquid-solid interface is formed instead of a solid-solid interface, so no electrolyte needs to be added, and the results show that the interface impedance between the anode and the LLZTO solid electrolyte can be reduced.
[0077] The present invention also provides a lithium battery, which uses the composite lithium metal negative electrode sheet described in the above technical solution as a negative electrode.
[0078] The present invention has no special restrictions on the positive electrode of the lithium battery, and preferably uses LiFePO4, LiNi 0.8 Mn 0.1 Co 0.1 Either O2 or LiCoO2 can be used.
[0079] In addition, for different types of lithium batteries, corresponding raw materials for preparing lithium batteries such as diaphragms, shells, etc., which are well known to those skilled in the art, can be used to obtain corresponding products according to conventional technical means for preparing lithium batteries. The present invention has no special restrictions on this.
[0080] The present invention provides a composite lithium metal negative electrode sheet and a preparation method and application thereof, which utilizes the in-situ growth of a lithium-philic MOF material on the surface of a porous solid electrolyte layer to greatly improve the interface wettability between molten lithium and the solid electrolyte, and has the following advantages:
[0081] (1) By using pore-forming agents, a micron-scale pore structure is formed on the surface of the solid electrolyte, thereby effectively increasing its specific surface area; this increased specific surface area not only increases the contact area of lithium metal, but also improves the conduction channel of lithium ions; the porous structure of the porous solid electrolyte layer can improve the bonding strength with both sides, and on the other hand, the intrusion and embedding of MOF-derived materials into the lithium metal layer can improve the overall conductivity; at the same time, the lithium affinity of MOF-derived materials and the pore structure of the porous solid electrolyte can promote the uniform deposition of lithium metal and improve the problem of lithium dendrite growth. The above factors interact with each other to achieve an overall synergistic effect, thereby enhancing the overall conductivity of the electrolyte.
[0082] (2) The addition of MOF improves the chemical contact between lithium metal and the solid electrolyte. The lithium-philic properties of MOF effectively reduce the interfacial binding energy between Li and the solid electrolyte, making it easier for lithium metal to bind to the electrolyte surface, forming a more stable interface.
[0083] The present invention provides a composite lithium metal negative electrode sheet and its preparation method and application; the composite lithium metal negative electrode sheet comprises a porous solid electrolyte layer, a lithium-philic layer composited on one side of the porous solid electrolyte layer, and a metal lithium layer composited on the other side of the porous solid electrolyte layer; the porous solid electrolyte layer has pores, the lithium-philic layer is at least partially embedded in the pores, and forms a conductive porous solid electrolyte skeleton with the porous solid electrolyte as a whole; the metal lithium layer at least partially fills the pores and forms a covering layer; the lithium-philic layer contains a metal oxide derived from MOF, and is formed by carbonization of MOF material grown in situ on the surface of the porous solid electrolyte layer. Compared with the prior art, the composite lithium metal negative electrode sheet provided by the present invention adopts a specific layer structure of specific materials to achieve overall better interaction, can significantly improve the interface wettability of metal lithium and solid electrolyte, inhibit dendrite growth, and has good stability.
[0084] At the same time, the preparation method provided by the present invention has a clear and concise overall process route, easily controllable conditions, and has broad application prospects.
[0085] To further illustrate the present invention, the following examples are used to provide a detailed description. The raw materials used in the following examples of the present invention are all commercially available; wherein, the preparation method of the LLZTO material is specifically as follows: according to the stoichiometric ratio, 6.75g LiOH·H2O, 3g La2O3, 1.75g ZrO2 and 0.25g Ta2O5 are mixed uniformly; the mixture is solid-phase sintered at a high temperature (about 960°C) for 6 hours to form an LLZTO powder material; the sintered LLZTO material is ball-milled to obtain a uniform LLZTO powder.
[0086] Comparative Example
[0087] (1) Preparation of porous LLZTO electrolyte slurry:
[0088] The prepared LLZTO powder (9 g), polyvinylidene fluoride film-forming agent (1 g), and starch (1 g) were mixed evenly, and 10 mL of anhydrous ethanol was added to mix; under stirring, the anhydrous ethanol was heated to 80-95° C. to fully dissolve the starch to form a uniform slurry; the slurry was cooled to room temperature, and then transferred to an oven and dried at 200° C. for 24 hours to remove ethanol to obtain a porous LLZTO electrolyte slurry.
[0089] (2) Forming and sintering of porous LLZTO electrolyte:
[0090] The porous LLZTO electrolyte slurry was pressed into a ceramic sheet with a diameter of 12 mm at 30 MPa, placed in an alumina crucible and completely covered with the mother powder, and sintered in a high-temperature muffle furnace at 1150 ° C for 16 h to obtain a porous LLZTO solid electrolyte with a porosity of 40%, a pore size of 10 μm, and a thickness of 25 μm. Figure 2 shown.
[0091] (3) Molten Li reaction treatment:
[0092] In a glove box filled with argon, 0.183 g of metallic lithium was heated to 200°C to obtain a metallic lithium melt, which was injected into the surface of the porous LLZTO. The liquid lithium entered the pores and the molten Li was immersed in the treated porous LLZTO electrolyte to ensure uniform deposition of lithium metal. The lithium metal loading per unit area of the porous LLZTO was 5 wt%, forming a good covering layer (40 μm thick), and finally forming a composite lithium metal negative electrode sheet.
[0093] Example 1
[0094] The composite lithium metal negative electrode sheet is prepared by the preparation method provided in the comparative example. The difference is that a layer of lithium-philic material is in situ grown on the surface of LLZTO. The overall process flow chart is shown in Figure 3 As shown:
[0095] (1) In situ growth of Sn-MOF:
[0096] 1.077g of SnCl2·2H2O was dissolved in 48ml of NN-dimethylformamide, 0.428g of terephthalic acid was dissolved in 12ml of anhydrous ethanol, and the two solutions were mixed and magnetically stirred until the solution became clear to obtain a mixed solution. The porous LLZTO solid electrolyte obtained in step (2) was then immersed in the above mixed solution, and then placed in a 100ml polytetrafluoroethylene reactor, kept warm in an oven at 120°C for 10h, taken out and dried, that is, Sn-MOF was in situ grown on the LLZTO surface; the product was then placed in a muffle furnace, heated to 400°C at a heating rate of 3°C / min for carbonization for 3h, and naturally cooled after being taken out to obtain a conductive porous SnO2@LLZTO skeleton with a thickness of 10μm.
[0097] Example 2
[0098] The composite lithium metal negative electrode sheet is prepared by the preparation method provided in the comparative example, the difference being that a layer of lithium-philic material is in situ grown on the surface of LLZTO:
[0099] (2) In situ growth of ZIF-67:
[0100] ZIF-67 was prepared by a room temperature standing method; 0.582 g of cobalt nitrate and 0.656 g of dimethylimidazole were dissolved in 50 ml of methanol and magnetically stirred to completely dissolve to obtain a mixed solution. The porous LLZTO solid electrolyte obtained in step (2) was then immersed in the above mixed solution and allowed to stand at room temperature for 24 h; ZIF-67@LLZTO was obtained after washing with deionized water and ethanol; the product was then heated to 350°C in a muffle furnace at a heating rate of 3°C / min for carbonization for 2 h, and then taken out and naturally cooled to obtain a conductive porous Co3O4@LLZTO skeleton with a thickness of 20 μm.
[0101] Example 3
[0102] The composite lithium metal negative electrode sheet is prepared by the preparation method provided in the comparative example, the difference being that a layer of lithium-philic material is in situ grown on the surface of LLZTO:
[0103] (3) In situ growth of Mn-MOF:
[0104] 0.098g of tetrahydrated manganese acetate and PVP (K-30, 0.3g) were dissolved in ethanol and H2O (5 / 5ml) and stirred to obtain a transparent solution. Then, ethanol and water (5 / 5ml) containing 1-3-5 trimesic acid (90mg) were slowly added to the above solution (10ml) with a pipette to obtain a mixed solution. The porous LLZTO solid electrolyte obtained in step (2) was then immersed in the above solution. Within 10 minutes, the obtained solution was continuously reacted at room temperature for 24 hours, washed three times with ethanol to obtain Mn-MOF@LLZTO, and finally dried in an oven at 60°C; then the temperature was raised to 450°C in air at a heating rate of 2°C / min for carbonization for 2h, and then taken out and naturally cooled to obtain a conductive porous Mn2O3@LLZTO skeleton with a thickness of 30μm.
[0105] Battery preparation for solid-state batteries:
[0106] (1) Preparation of lithium iron phosphate positive electrode sheet: 0.15g of active material, carbon black and polyvinylidene fluoride (PVDF) were mixed and ground in a mortar at a ratio of 7:2:1 for one hour. Then, N-methylpyrrolidone was used as the solvent and the grinding process was performed again for 30 minutes. The slurry was then evenly coated on the aluminum foil with a scraper to ensure that the coating thickness was 100μm. Subsequently, the prepared positive electrode sheet was placed in an oven at 60°C for 4h of drying to ensure that the solvent was effectively volatilized. Subsequently, the positive electrode sheet was transferred to a drying oven at 120°C and vacuum dried overnight to further remove residual solvent and moisture. Finally, the dried positive electrode sheet was cut into discs with a diameter of 14mm using a slicer, weighed and placed in a glove box for subsequent use.
[0107] (2) Assemble the button cell in a glove box filled with argon. See the schematic diagram for the structure. Figure 4 As shown, 1 is the negative electrode shell, 2 is the spring, 3 is the gasket, 4 is the composite lithium metal negative electrode sheet, 5 is the diaphragm, 6 is the positive electrode sheet, and 7 is the positive electrode shell; ensure that the water and oxygen content therein are always kept below 0.01ppm. In addition, 3ml of ester electrolyte (LiPF6) is dripped on both sides of the diaphragm. The full battery is prepared in the order of composite lithium metal negative electrode sheet-diaphragm-lithium iron phosphate positive electrode sheet, wherein the lithium-philic layer side of the composite lithium metal negative electrode sheet is in contact with the diaphragm.
[0108] Performance Testing:
[0109] All full batteries were placed in a constant temperature box at 60°C, and their charge and discharge performance was tested within a voltage range of 2.5 to 4.0V (charging cut-off voltage was 4.0V, and discharging cut-off voltage was 2.5V) using the Blue Electric Battery Test System, which included constant current charge and discharge long cycles, rate performance tests, and CV tests.
[0110] 1) The long cycle test process is as follows: ① stand for 5 minutes, ② charge to 4.0V at 0.2C constant current, ③ stand for 5 minutes, ④ discharge to 2.5V at 0.2C constant current, ⑤ cycle steps 1) to 4) for x cycles (x is 30, 80 or 100), record the discharge capacity of each cycle, and calculate the average discharge capacity of x cycles;
[0111] 2) The rate test process is as follows: ① Stand still for 5 minutes, then charge and discharge at 0.2C constant current for 10 cycles, 1.0C constant current for 10 cycles, 2.0C constant current for 10 cycles, 3.0C constant current for 10 cycles, 2.0C constant current for 10 cycles, 1.0C constant current for 10 cycles, and 0.2C constant current for 10 cycles, and record the discharge capacity and charge and discharge efficiency of each cycle. The results are as follows Figure 6 As shown. ;
[0112] 3) CV test parameters are as follows: scanning voltage range is 2.5-4.2 V, scanning rate is 0.1 mV / s, and scanning times is 3 times.
[0113] The experimental results show that: as can be seen from Table 1, Examples 1, 2, and 3 all show better performance in terms of cycle performance than the comparative example, which may be due to the porous solid electrolyte in the examples being covered with a lithium-philic layer. The lithium-philic layer significantly improves the performance and safety of the battery by improving wettability, inhibiting lithium dendrite growth, and increasing capacity retention.
[0114] The full battery assembled by matching the composite negative electrode sheet (Co3O4@LLZTO@Li) in Example 2 with the LiFePO4 positive electrode was subjected to long cycle, rate and CV tests. Figure 5The long cycle test results of Co3O4@LLZTO@Li||LFP full battery at 0.2C rate are shown. After 80 cycles, the full battery still maintains an average discharge capacity of 149.4mAh / g; Figure 6 The rate test results of Co3O4@LLZTO@Li||LFP full battery at 0.2C~3C are shown. As can be seen from the figure, the full battery platform is relatively stable and has good rate reversibility; the CV test results are as follows Figure 7 As shown in the figure, it can be seen that the capacity-voltage curves of the first three cycles of the Co3O4@LLZTO@Li||LFP full battery almost completely overlap, indicating that the voltage polarization of the full battery is small during the charge and discharge process and the platform is very stable.
[0115] The following table lists the cycle performance of full batteries assembled into button batteries in specific comparative examples and implementation cases.
[0116] Table 1 Experimental data table
[0117] Material Loop Condition Cycle number Average discharge capacity (mAh / g) Comparative Example LLZTO@Li 0.2C 30 143.2 Example 1 <![CDATA[SnO2@LLZTO@Li]]> 0.2C 100 155.3 Example 2 <![CDATA[Co3O4@LLZTO@Li]]> 0.2C 80 149.4 Example 3 <![CDATA[Mn2O3@LLZTO@Li]]> 0.2C 100 145.6
[0118] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A composite lithium metal negative electrode sheet, characterized in that: The porous solid electrolyte layer comprises a lithium-philic layer composited on one side of the porous solid electrolyte layer, and a metal lithium layer composited on the other side of the porous solid electrolyte layer; the porous solid electrolyte layer has pores, the lithium-philic layer is at least partially embedded in the pores, and forms a conductive porous solid electrolyte skeleton with the porous solid electrolyte as a whole; the metal lithium layer at least partially fills the pores and forms a covering layer; The lithium-philic layer contains a metal oxide derived from a MOF and is formed by carbonizing a MOF material grown in situ on the surface of the porous solid electrolyte layer.
2. The composite lithium metal negative electrode sheet according to claim 1, characterized in that: The porous solid electrolyte layer has a porosity of 40% to 80%, a pore diameter of 1 μm to 20 μm, and a thickness of 25 μm to 30 μm.
3. The composite lithium metal negative electrode sheet according to claim 1, characterized in that: The MOF material is selected from one or more of Zr-MOF, Sn-MOF, Mn-MOF, ZIF-8, ZIF-67, MIL-101, and MIL-100.
4. The composite lithium metal negative electrode sheet according to claim 1, characterized in that: The thickness of the composite lithium metal negative electrode sheet is 40 μm to 80 μm; The thickness of the lithium-philic layer is 10 μm to 20 μm; The thickness of the conductive porous solid electrolyte skeleton is 30 μm to 50 μm; The thickness of the covering layer is 10 μm to 30 μm.
5. A method for preparing a composite lithium metal negative electrode sheet according to any one of claims 1 to 4, characterized in that: The following steps are involved: a) mixing a solid electrolyte, a pore-forming agent, a film-forming agent and a solvent, and drying the mixture to obtain a mixed slurry; and then sequentially forming and sintering the mixed slurry to obtain a porous solid electrolyte layer; b) in-situ growing a MOF material on the surface of the porous solid electrolyte layer obtained in step a), and obtaining a conductive porous solid electrolyte skeleton after carbonization; c) melting and pouring metallic lithium into the conductive porous solid electrolyte skeleton obtained in step b) to fill the pores and form a covering layer to obtain a composite lithium metal negative electrode sheet.
6. The preparation method according to claim 5, characterized in that: The solid electrolyte in step a) is LLZTO material; the preparation method of the LLZTO material is specifically as follows: LiOH·H2O, La2O3, ZrO2 and Ta2O5 are mixed, solid-phase sintered and then ground to obtain LLZTO material; The solid phase sintering is carried out at a temperature of 900° C. to 1000° C. and for a time of 4 to 6 hours.
7. The preparation method according to claim 5, characterized in that: In step a), the pore-forming agent is selected from one or more of glucose, sucrose, urea, starch, and citric acid; the film-forming agent is selected from polyethersulfone and / or polyvinylidene fluoride; the solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, and anhydrous ethanol; The mass ratio of the solid electrolyte, pore former and film former is 1:(0.1-0.2):(0.05-0.2); The drying temperature is 150°C to 250°C and the drying time is 20h to 30h; The molding pressure is 15MPa to 300MPa; The sintering temperature is 1000° C. to 1200° C., and the sintering time is 6 h to 24 h.
8. The preparation method according to claim 5, characterized in that: The in-situ growth method in step b) is: subjecting the porous solid electrolyte to a hydrothermal reaction in a MOF precursor solution; the hydrothermal reaction temperature is 20° C. to 180° C., and the time is 8 h to 24 h; The carbonization heating rate is 1°C / min to 5°C / min, the temperature is 280°C to 500°C, and the time is 2h to 4h.
9. The preparation method according to claim 5, characterized in that: The process of melt infusion in step c) is specifically as follows: After the conductive porous solid electrolyte skeleton is brought into contact with the metal lithium sheet, the metal lithium sheet is heated to melt, and the molten metal lithium partially fills the pores through adsorption to form a covering layer.
10. A lithium battery, characterized in that: The composite lithium metal negative electrode sheet according to any one of claims 1 to 4 is used as the negative electrode.
Citation Information
Patent Citations
Lithium metal secondary battery based on porous ceramic composite lithium metal negative electrode and preparation method thereof
CN110890530A
Method for preparing three-dimensional metal lithium negative electrode by using MOFs derivative
CN114122332A
Negative current collector, preparation method thereof, negative pole piece with negative current collector, and lithium secondary battery
CN115842133A
Composite solid electrolyte based on metal organic framework array as well as preparation method and application of composite solid electrolyte
CN116666747A
Garnet type solid electrolyte and lithium metal negative electrode interface contact modification method
CN117855395A